Changes in complacency to adherence to COVID-19 preventive behavioral measures and mental health after COVID-19 vaccination among medical and dental healthcare professionals - Farooq Ahmad Chaudhary; Osama Khattak; Muhammad Danial Khalid; Muhammad Usman Khattak; Farida Habib Khan; Fahmida Khatoon; Rana Aboras; Reem Falah Alshammari; Azhar Iqbal; Ali Azhar Dawasaz; Mohammad Shahul Hameed; Mohmed Isaqali Karobari (Taylor & Francis Group, 2024)
Medical and dental professionals should continue to adhere to preventive measures after COVID-19 vaccination due to their increased risk of exposure to the virus, particularly as new variants emerge that may heighten their risk perception and susceptibility. Therefore, this study aimed to explore the effects of COVID-19 vaccination on complacency to adherence to COVID-19 preventive behavioral measures and mental health among medical and dental professionals. In this cross-sectional study 410 medical and dental professionals were recruited from different medical and dental hospitals in Islamabad, Pakistan. The data was collected using a valid and reliable questionnaire comprising of three sections (socio-demographic, information of preventive behaviors performance against COVID-19 after vaccination, mental health status). A chi-square test and ordinal logistic regression were used for analysis. Post COVID-19 vaccination there was decrease in the frequency of use of hand washing, sanitizers (70.2%), and social distancing (60.5%), however greeting with a handshake (58.8%) and use of public transport (45.9%) seen upward trend among participants. Only face mask usage post-vaccination was statistically significant (p < .05) in association with age, marital status, and years of working Experience. The greatest decrease in the usage of masks after COVID-19 vaccination was seen in age group of 10-30 (41.7%) and working experience group of 0-5 years (39.7%). All the preventive behaviors are statistically significant (p < .05) associated with the mental status of the participants except online shopping and use of public transport. These results indicate the presence of vaccination-induced complacency in adherence to COVID-19 preventive behavioral measures among healthcare professionals.